A Study of Beliefs about EMI Programmes in a Galician University - Rodríguez Rodríguez, Yonay (Miscelánea: A Journal of English and American Studies, 2025)
The beliefs that learners hold are a key variable in language learning, and from a socio-cultural perspective, learner beliefs are connected to the context in which learning takes place. This study, which forms part of a more extensive project on beliefs about English as a foreign language (EFL), explores the views of a group of students and instructors at the University of Santiago de Compostela (USC) regarding content learning in English. The beliefs of 373 students and instructors were measured by means of a questionnaire and interview. Despite indicating a generally positive predisposition towards EMI programmes, the responses varied based on the academic field of the course content, students’ previous language-learning experience and the type of English instruction used in teaching. In addition, the data revealed a series of issues concerning the implementation of EMI programmes at the USC. This study is the first of its type to be conducted at this institution and one of the few in Galicia. Findings from the study underscore the context-specific nature of beliefs in general while also drawing the USC, together with other Spanish and foreign academic institutions, into a broader assessment and discussion of EMI programmes.
Keywords: beliefs; context; English as a Medium of Instruction (EMI); programme implementation